2014
DOI: 10.1007/s00421-014-3005-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake kinetics in trained adolescent females

Abstract: Little evidence exists with regard to the effect that exercise training has upon oxygen uptake kinetics in adolescent females. PURPOSE: The aim of the study was to compare 2 o V  and muscle deoxygenation kinetics in a group of trained (Tr) and untrained (Utr) female adolescents. METHOD: Twelve trained (6.4 ± 0.9 years training, 10.3 ± 1.4 months per year training, 5.2 ± 2.0 hours per week) adolescent female soccer players (Age: 14.6 ± 0.7 years) were compared to a group (n=8) of recreationally active adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
5
11
0
Order By: Relevance
“…With faster taus relating to a greater volume and an improved ability to maintain high speed activities during youth soccer match-play. Furthermore, research into adolescent male and female soccer players has demonstrated faster VO kinetics in soccer trained individuals in comparison to their untrained counterparts (29,37). Current results also support previous research which highlights faster taus in younger populations, with such measures becoming progressively slower (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…With faster taus relating to a greater volume and an improved ability to maintain high speed activities during youth soccer match-play. Furthermore, research into adolescent male and female soccer players has demonstrated faster VO kinetics in soccer trained individuals in comparison to their untrained counterparts (29,37). Current results also support previous research which highlights faster taus in younger populations, with such measures becoming progressively slower (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…However, it was also suggested that these findings may reflect the presence of a maturational threshold below which a significant physiological response to training was not manifest (61). In contrast to this notion and the earlier studies, more recent, methodologically rigorous, studies report a significant influence of training status on the V  O2 kinetics of both prepubertal children (80,112) and pubertal adolescents (78,81,104), although these differences were still restricted to the temporal parameters with no influence of the magnitude of the V  O2 slow component. Perhaps surprisingly given the relevance to training guidelines and performance (33), no studies have directly addressed the question of sex differences in the response of V  O2 kinetics to training.…”
Section: Influence Of Training On Pulmonary V  O2 Kineticsmentioning
confidence: 64%
“…Specifically, a faster V̇O2 kinetic time constant was reported in trained compared to untrained children (Winlove et al, 2010) with no differences found in two other studies (Cleuziou et al, 2002, Obert et al, 2000. Adolescent studies have, however, found training to be associated with a faster V̇O2 kinetic time constant (Marwood et al, 2010, McNarry et al, 2011c, Unnithan et al, 2015. A faster V̇O2 kinetic time constant was also observed following a 6-week High-Intensity Interval Training (HIIT) intervention in obese children (McNarry et al, 2015b), though it is noteworthy that no influence of HIIT was found in the normal weight children.…”
Section: Introductionmentioning
confidence: 92%
“…Indeed, in pre-pubertal children, Winlove et al (2010) reported a faster V̇O2 kinetic time constant in trained swimmers in comparison to their untrained peers, whilst in contrast, two studies reported no difference between trained and untrained pre-pubertal children (Cleuziou et al, 2002, Obert et al, 2000. Moreover, in adolescents, training was associated with a faster V̇O2 kinetic time constant than their untrained peers (Marwood et al, 2010, McNarry et al, 2011c, Unnithan et al, 2015. The conflicting results may be explained by different modalities between training and experimental measures.…”
Section: Training Effects Of V̇o2 Kineticsmentioning
confidence: 98%
See 1 more Smart Citation